A multiple time step scheme for multiresolved models of Macromolecules. Issue 16 (26th March 2014) - Di Pasquale, Nicodemo; Gowers, Richard J.; Carbone, Paola
<x xml:space="preserve">Abstract</x> In hybrid particle models where coarse‐grained beads and atoms are used simultaneously, two clearly separate time scales are mixed. If such models are used in molecular dynamics simulations, a multiple time step (MTS) scheme can therefore be used. In this manuscript, we propose a simple MTS algorithm which approximates for a specific number of integration steps the slow coarse‐grained bead–bead interactions with a Taylor series approximation while the atom–atom ones are integrated every time step. The procedure is applied to a previously developed hybrid model of a melt of atactic polystyrene (di Pasquale, Marchisio, and Carbone, J. Chem. Phys. 2012, 137, 164111). The results show that structure, local dynamics, and free diffusion of the model are not altered by the application of the integration scheme which can confidently be used to simulate multiresolved models of polymer melts. © 2014 Wiley Periodicals, Inc.